Sistem Sadar dan Bank Sampah untuk Pemulihan Berkelanjutan di Desa Simomulyo Pada Masa Normal Baru - Ayyub Ihza Gutawa; Alfan Afiyudin; Ghaly Atha Maulana; Prastyo Utomo; Michael Aria Irawan; Marijatul Maghfiroh; Selviana Rohmatus Dania; Angelia Hayuning Ariffa; Maulida Dewi Amanda; Mohammad Shodiq Wahyu Riamto; Dwi Sukma Donoriyanto; Joumil Aidil (Jurnal Nusantara Berbakti, 2024)
The pandemic era that occurred in 2020 is a new history in human civilization. The emergence of the pandemic has limited interaction between humans and the surrounding environment. Limited interaction during the pandemic is manifested in the social distancing program, indirectly this program can reduce the sense of social concern, kinship and togetherness between residents. Not only does it have an impact on social welfare, this program will also limit buying and selling activities in markets and local village environments. Thus affecting the level of economic welfare of local communities. The pandemic era that has ended has not been able to restore the economy and health of the affected communities, so various individual and group efforts still need to be made that can increase people's income. Some of the problems above are the background and reasons for choosing Simomulyo Village as our KKN object. Simomulyo village has a very strategic location because it is located in the city center and has a fairly large market. Of course, this condition causes Simomulyo village to receive a significant impact from the pandemic period to the post-pandemic period. To solve existing problems, we and the Simomulyo Village community will work together to maximize the benefits of implementing the waste bank program. The success of this optimization is marked by increased awareness and insight of the village community regarding waste that is ready to be recycled and sold to increase village income. The hope is that, apart from being useful in creating a healthy environment, the waste bank program will also be useful in improving economic and social welfare for the people of Simomulyo Village. This is realized in the form of a waste bank account which is accumulated into cash to ensure the smooth implementation of several village activities.